2014
DOI: 10.1080/10106049.2014.927535
|View full text |Cite
|
Sign up to set email alerts
|

Neural networks-based simulation of land cover scenarios in Doon valley, India

Abstract: Land cover transformation is one of the foremost aspects of human-induced environmental change, having an extensive history dating back to antiquity. The present study aims to simulate the process of land cover change based on different policybased scenarios so as to provide a basis for sustainable development in Doon valley, India. For this purpose, an artificial neural network-based spatial predictive model was developed for the Doon valley. The predictive model generated future land cover patterns under thr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 42 publications
0
9
0
Order By: Relevance
“…Applied to LC datasets, the aim is to use these automated, statistical methods to identify and analyze spatial patterns that have resulted from underlying processes of LCC over time. ML methods employed in LC simulations and assessments have previously included neural networks (NNs) [13], decision trees (DTs), and support vector machines (SVMs) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Applied to LC datasets, the aim is to use these automated, statistical methods to identify and analyze spatial patterns that have resulted from underlying processes of LCC over time. ML methods employed in LC simulations and assessments have previously included neural networks (NNs) [13], decision trees (DTs), and support vector machines (SVMs) [14].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have revealed that the integrated MultiLayer Perceptron-Markov chain analysis (MLP-MCA) method is a robust tool to quantify and model the spatio-temporal LULC changes that combines remote sensing and GIS efficiently (Ahmed & Ahmed, 2012;Mishra et al, 2014;Ozturk, 2015). In the MLP-MCA hybrid model, the MLP neural network is trained by supervized backpropagation (BP) algorithm with efficient generalization capability for each LULC transition and simulation (Maithani, 2015), while the MCA model determines transition probability areas to predict likely LULC changes in the future (Dadhich & Hanaoka, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Each model has advantages and disadvantages [27,30]. Thus, various hybrid models have also been adapted to simulate urban growth [19,22,25,[31][32][33][34][35][36]. Determining which hybrid model provides the best results is difficult because each study reaches unique conclusions.…”
mentioning
confidence: 99%